Pemberdayaan Masyarakat Dalam Pengelolahan Sampah Melalui Pengadaan Tempat Pembuangan Sampah di Desa Ampera Dusun 1 Kecematan Palolo Kabupaten Sigi Provinsi Sulawesi Tengah - Sabir, Sabir; Kawiri, Hendrik; Wahyudi, Wahyudi; Nurhasana, Dwi; Abdullah, Serlih; Pramesti Heriyanto, Diajeng Dita Nur; Ambosakka, Dhemanda H.; Sari Jasi, Alyu Indah; Masahengke, Romildah Oktovin; Sam, Jein; Magfira, Magfira (Abdimas Indonesian Journal, 2025)
Indonesia is one of the world's second largest waste producers after China. According to data from the Ministry of Environment, there is a total of 33,320,745.45 tons of waste per year, and 13,640,631.44 tons of waste are unmanaged. Community service activities in Ampera Village aimed to increase public understanding of waste management through education and direct implementation of waste management. This activity involved all residents of Ampera Village, Dusun 1, as well as village officials, pre-test and post-test of knowledge about waste, and a question-and- answer session. The results showed an increase in public knowledge after being educated through lectures and waste management videos, with a better proportion of understanding of waste management. Community and village support is very important for the success of this activity, although there are challenges in participation. Continuous education is expected to further increase awareness of waste management to maintain public.